Growth and inactivation of Salmonella enterica and Listeria monocytogenes in broth and validation in ground pork meat during simulated home storage abusive temperature and home pan-frying - Wang, Xiang; Lahou, Evy; De Boeck, Elien; Devlieghere, Frank; Geeraerd, Annemie; Uyttendaele, Mieke (Frontiers in Microbiology, 2015)
Ground pork meat with natural microbiota and inoculated with low initial densities (1-10 or 10-100 CFU/g) of Salmonella enterica or Listeria monocytogenes was stored under abusive temperature at 10°C and thermally treated by a simulated home pan-frying procedure. The growth and inactivation characteristics were also evaluated in broth. In ground pork meat, the population of S. enterica increased by less than one log after 12-days of storage at 10°C, whereas L. monocytogenes increased by 2.3 to 2.8 log units. No unusual intrinsic heat resistance of the pathogens was noted when tested in broth at 60°C although shoulders were observed on the inactivation curves of L. monocytogenes. After growth of S. enterica and L. monocytogenes at 10°C for 5 days to levels of 1.95 log CFU/g and 3.10 log CFU/g, respectively, in ground pork meat, their inactivation in the burger subjected to a simulated home pan-frying was studied. After thermal treatment S. enterica was undetectable but L. monocytogenes was recovered in three out of six of the 25 g burger samples. Overall, the present study shows that data on growth and inactivation of broths are indicative but may underestimate as well as overestimate behavior of pathogens and thus need confirmation in food matrix conditions to assess food safety in reasonably foreseen abusive conditions of storage and usual home pan-frying of of meat burgers in Belgium.